Dinamika Hak Asuh Anak di Negara Al- Jazair dan Indonesia: Analisis Perbandingan terhadap Regulasi dan Praktik Sosial - Noer Zaini Khalis; Sukiati Sukiati; Iwan Iwan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study analyzes the dynamics of child custody (hadhanah) in Algeria and Indonesia through a comparative examination of legal regulations and social practices in both countries. This topic is important because post-divorce child custody is closely related to the protection of children’s rights, legal certainty, and the application of the principle of the best interests of the child. The study employs a normative legal research method with a comparative law approach. Data were collected through a literature review of legislation, Islamic legal literature, scholarly articles, and relevant legal documents. The findings indicate that both Indonesia and Algeria use Islamic law as a foundation in regulating hadhanah, although their legal constructions differ. In Indonesia, the Compilation of Islamic Law prioritizes custody rights for mothers for children who are not yet mumayyiz. In contrast, Algeria, which is strongly influenced by the Maliki school of thought, provides more detailed rules regarding the hierarchy of custodians and custody conditions. In practice, both countries face similar challenges, including custody disputes after divorce, considerations of child welfare, and changes in modern family structures. Nevertheless, the best interests of the child remain the primary principle in custody decisions. The study concludes that differences in hadhanah regulations are shaped by variations in Islamic jurisprudence, national legal systems, and social contexts, highlighting the need to strengthen child protection mechanisms.